Resistive jet simulations extending radially self-similar magnetohydrodynamic models - Čemeljić, M.; Gracia, J.; Vlahakis, N.; Tsinganos, K. (Monthly Notices of the Royal Astronomical Society, 2008)
Numerical simulations with self-similar initial and boundary conditions provide a link between theoretical and numerical investigations of jet dynamics. We perform axisymmetric resistive magnetohydrodynamic (MHD) simulations for a generalized solution of the Blandford & Payne type, and compare them with the corresponding analytical and numerical ideal MHD solutions. We disentangle the effects of the numerical and physical diffusivity. The latter could occur in outflows above an accretion disc, being transferred from the underlying disc into the disc corona by MHD turbulence (anomalous turbulent diffusivity), or as a result of ambipolar diffusion in partially ionized flows. We conclude that while the classical magnetic Reynolds number Rm measures the importance of resistive effects in the induction equation, a new introduced number, Rβ = (β/2)Rm with β the plasma beta, measures the importance of the resistive effects in the energy equation. Thus, in magnetized jets with β < 2, when Rβ <~ 1 resistive effects are non-negligible and affect mostly the energy equation. The presented simulations indeed show that for a range of magnetic diffusivities corresponding to Rβ >~ 1, the flow remains close to the ideal MHD self-similar solution.
Keywords: Astrophysics; ISM: jets and outflows; MHD; stars: magnetic fields; stars: pre-main-sequence